Microbiological profile of biofilm in the orotracheal tube of extubated patients: Literature review (Research, Society and Development, 2021)
Inpatient oral biofilm, also colonized by respiratory pathogens capable of causing lung infection, associated with poor cleaning may contaminate the orotracheal tube, increasing the risk of developing ventilator-associated pneumonia (VAP) in critically ill patients. The aim of this study was to review the literature that presents the microbiological profile of oral biofilm in the orotracheal tube of extubated patients admitted to Intensive Care Unit (ICU). Thus, we sought to investigate the presence of respiratory pathogens in the oral cavity of patients in ICU and data on the participation of oral condition in the establishment of VAP. In order to delineate the study, the PICO criteria were used to perform a systematic review. Of the 72 articles found, 5 were selected that best met the eligibility profile, especially those that would provide better confidence, strength, consistency and those with the lowest error rates. The studies presented results for the microbiological profile of the endotracheal tube that is colonized by oral microorganisms, mainly by Streptococcus spp. The maturation of this biofilm promoted a synergy of these with more virulent bacteria, mainly of Staphylococcus aureus, Pseudomonas aeruginosa, capable of promoting VAP. It was concluded that the microbiological profile of the oral biofilm in the orotracheal tube of extubated patients admitted to ICU is oral bacteria, suggesting the necessity of maintenance of oral hygiene during mechanical ventilation to reduce the reservoir of respiratory pathogens within the dental biofilm and consequently in the endotracheal tube.